2005
DOI: 10.1063/1.2087447
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ca-montmorillonite hydrates: A computer simulation study

Abstract: Classic simulations are used to study interlayer structure, swelling curves, and stability of Camontmorillonite hydrates. For this purpose, N PzzT and µPzzT ensembles are sampled for ground level and given burial conditions. For ground level conditions, a double layer hydrate having 15.0Å of basal spacing is the predominant state for relative vapor pressures (p/p0) ranging in 0.6-1.0. A triple hydrate counting on 17.9Å of interlaminar distance was also found stable for p/p0=1.0. For low vapor pressures, the sy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
3
14
0
1
Order By: Relevance
“…It is interesting to mention that a similar trend has been described recently in the studies of mineral clays swelling 30,31 . Namely, Smith et al 31 reported the simulation results of hydrated Na-smectites with variable layer charge.…”
Section: Resultssupporting
confidence: 83%
“…It is interesting to mention that a similar trend has been described recently in the studies of mineral clays swelling 30,31 . Namely, Smith et al 31 reported the simulation results of hydrated Na-smectites with variable layer charge.…”
Section: Resultssupporting
confidence: 83%
“…The problem is complicated by the structural changes occurring upon insertion 10,11 or intercalation. 12,13 In many cases mechanical strain generated in the intercalation/ deintercalation cycles induces structural as well as volume changes in the electrode material, leading to fracturing, cracking and even crumbling, and thereby to electrode irreversibility upon cycling.…”
Section: Introductionmentioning
confidence: 99%
“…As can be seen in Table III, the distance of 14.67Å before heat treatment is reduced to around 10.00Å after heating until 250 • C, showing a decrease of around 4.67Å due to loss of water molecules, particularly in the interlaminar region. According to the literature, calcium montmorillonites with interlaminar distances around 15Å, as in this case, have a double layer of water molecules in the interlaminar region [16]. Since the average size of a water molecule is around 2.02Å, the decrease in the interlaminar distance would be due to the removal of two layers of water, generating the dehydrated phase of Ca-montmorillonite and the modification of its structure.…”
Section: Resultsmentioning
confidence: 87%